A Review of Multimedia Projects in Education Design, Producing, and Assessing - Hossein Zangeneh; Zahra Bahrami (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The purpose of this study was to review and criticize the “Multimedia Projects in Education: Design, Producing, and Assessing” book. Therefore, analytical-documentary methods were used. The book was written by Karen S. Ivers and Ann E. Barron in 2010 and translated by Khadijeh Aliabadi and Esmail Aslani in 2016 and published by Booka Publisher. This paper has been compiled by applying the method of document analysis and reviewing the scope of the book’s merits and shortcomings and reveals that the text has shortcomings in spite of the acceptable consistency with the original text, refinement and fluency, and the availability of specially qualified vocabulary including the lack of designing a teaching-learning strategy and analyzing multiple intelligences during the process of the idea to evaluation, lack of operational and precise strategies for implementing the cooperative learning strategy (collaborative learning), the lack of attention to the details of the steps and activities of each proposed model, lack of attention to the conceptual separation of the flowchart with the content structure and the inability to select some appropriate titles according to the content. The book’s usefulness as a teaching guide for a collaborative multimedia project learning strategy is high as a source of training in electronic content production courses at the undergraduate and even master’s degree courses. Therefore, it is suggested that writers improve their formal, structural, and content defects by resolving them.